Late effects in survivors of high‐risk neuroblastoma following stem cell transplant with and without total body irradiation. Issue 3 (31st December 2021) - Hobbie, Wendy L.; Li, Yimei; Carlson, Claire; Goldfarb, Samuel; Laskin, Benjamin; Denburg, Michelle; Goldmuntz, Elizabeth; Mostoufi‐Moab, Sogol; Wilkes, Jennifer; Smith, Karen; Sacks, Nancy; Szalda, Dava; et al.
Abstract: Background: Neuroblastoma is the most common extracranial solid tumor in children. Those with high‐risk disease are treated with multimodal therapy, including high‐dose chemotherapy, stem cell transplant, radiation, and immunotherapy that have led to multiple long‐term complications in survivors. In the late 1990s, consolidation therapy involved myeloablative conditioning including total body irradiation (TBI) with autologous stem cell rescue. Recognizing the significant long‐term toxicities of exposure to TBI, more contemporary treatment protocols have removed this from conditioning regimens. This study examines an expanded cohort of 48 high‐risk neuroblastoma patients to identify differences in the late effect profiles for those treated with TBI and those treated without TBI. Procedure: Data on the study cohort were collected from clinic charts, provider documentation in the electronic medical record of visits to survivorship clinic, including all subspecialists, and ancillary reports of laboratory and diagnostic tests done as part of risk‐based screening at each visit. Results: All 48 survivors of BMT for high‐risk neuroblastoma had numerous late effects of therapy, with 73% having between five and 10 late effects. TBI impacted some late effects significantly, including growth hormone deficiency (GHD), bone outcomes, and cataracts. Conclusion: Although high‐risk neuroblastoma survivors treated with TBI have significant late effects, those treated without TBI also continue to have significant morbidity related to high‐dose chemotherapy and local radiation. A multidisciplinary care team assists in providing comprehensive care to those survivors who are at highest risk for significant late effects.